Kebijakan Relokasi Warga di Sekitar Proyek Strategis Nasional Toba Caldera Resort: Undang-Undang Nomor 2 Tahun 2012 dan Perspektif Siyasah Dusturiyah - Rasyid, Rahmat; Khalid, Khalid (Kartika: Jurnal Studi Keislaman, 2025)
This study examines the policy of relocating residents living around the Toba Caldera Resort National Strategic Project (PSN), which is part of the development of the Lake Toba super-priority tourism destination. The research focuses on two main aspects: a legal analysis based on Law Number 2 of 2012 concerning Land Acquisition for Development in the Public Interest, and a review from the perspective of Siyasah Dusturiyah, an Islamic political jurisprudence that emphasizes the relationship between public policy, authority, and public welfare. This research employs a normative juridical method using statutory and conceptual approaches, with data collected through library research on legislation, court decisions, academic journals, and classical and contemporary literature on fiqh siyasah. The findings indicate that, normatively, the relocation policy has a clear legal framework regarding compensation and the protection of affected residents’ rights. However, in practice, issues remain, including limited public participation, information imbalance, and unequal compensation. From the perspective of Siyasah Dusturiyah, relocation policies should uphold justice, deliberation, and public welfare to prevent social and economic harm to affected communities